Hoping Of Zakat Reinforcing Philanthropy In Indonesia - Muhamad Fauzi; Agus Gunawan (LPPM ISNJ Bengkalis, 2022)
Indonesia is the most generous country by donating unknown people, money donations, and volunteer activities based on the World Giving Index by the Muslim majority population, contributing to the poor's socioeconomic, welfare, and empowerment. Zakat is a philanthropic activity with great potential and utilization, but there is a gap between its revenue potential and its realization. This research aims to describe the hope that zakat will strengthen philanthropy in Indonesia. The research method uses a qualitative descriptive approach and reports from zakat institution's secondary data sources. The results showed 81 amil zakat institutions and 491 zakat bureaus as zakat collection institutions increased in zakat collection by 26%, consisting of zakat fitrah, zakat mal income, zakat institutions, and individual zakat as 5.1 million people and corporate zakat as 36,000. Zakat through e-zakat or bank transfers and e-payments reached 93% during the Covid-19 pandemic. Zakat gives excellent hope to society's welfare through government and stakeholder regulations that can reduce the level of poverty. Zakat IDR 10.2 trillion gives hope to 23 million people and frees 15759 from the poverty line with better distribution effectiveness; the philanthropic hope of strengthening zakat in Indonesia has provided benefits and community welfare.